PENGARUH TEKNIK RELAKSASI BENSON TERHADAP TINGKAT KECEMASAN PASIEN PRE TINDAKAN TREADMILL TEST - SUSANTI ROHMAH KURNIA (LPPMK STIKES Widyagama Husada, 2022)
ABSTRACT BACKGROUND : Treadmill test is one of the diagnoses for heart disease that can cause anxiety. Non-pharmacological therapy for anxiety is BensonIrelaxation, which is relaxationithat combines relaxation response techniques and individual belief systems. OBJECTIVE: This study aims to determine the effect of Benson's relaxation technique on the anxiety level of pre-treadmill test patients at Dr. Saiful Anwar Hospital Malang. METHOD : Thisi study usedi a pre-experimental one group pre- and post-test design. Sampling using purposive sampling with a sample of 52 respondents. The instrument used is STAI (State-TraitiAnxiety Inventory)i which contains 20 state anxiety items and 20 trait anxiety items. Thei instrument used is STAI (State-TraitiAnxiety Inventory)iwhich contains 20 state anxiety items and 20 trait anxiety items. RESULT : From the results of the Wilcoxon test, it was found that there was a significant effect on decreasing levels of anxiety before the treadmill test with a p value of 0.000. CONCLUSION : It was concludedithat thereiwas an effect of Benson's relaxation onithe anxiety level of pre-treadmill patients. Benson relaxation is expected to be one ofi the non-pharmacologicali intervention optionsi to reducei anxiety levelsiand facilitatei patients undergoing the treadmill test to perform Benson relaxation. KEYWORDS: iAnxiety, Benson Relaxation,Treadmill Test